ECO-BRANDING PADA PRODUK KOSMETIK LOKAL INDONESIA - Kurnia Budhy Scorita; Aisyah Pia Asrunputri (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Bina Insani, 2022)
Local Indonesian cosmetic products are currently starting to dominate in their own country, there are many choices of cosmetic / skincare products in Indonesia, only those that carry the concept of eco branding are still small, even though currently young people in Indonesia have a very high interest in environmental concepts, and this used by some cosmetic manufacturers by promoting environmentally friendly cosmetic products. Of course the eco-branding concept applied aims to increase trust and interest in buying products. This is certainly an interesting theme to study. This research method uses a qualitative research approach with descriptive analysis of literature reviews in national journals systematically from eco-branding theory using the Publish or Perish application and VOS Viewer. The results of the study show that eight Indonesian local cosmetics have fulfilled aspects of the eco-branding theory. Keywords: Eco Branding, Cosmetic Products, Environmentally Friendly